Analysis Illumination of Public Street Lighting on Street Jenderal Sudirman in Pemalang Regency - Arief Bagus Dermawan; Noor Hudallah; Riana Defi Mahadji Putri; Tatyantoro Andrasto (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Public street lighting is a complement to the road and is placed on the left or right side of the road or in the middle of the median of the road to illuminate the road. The public street lighting that has been operating is usually rarely maintained, and problems will arise in the street lighting that can reduce the illumination value. This study aims to determine the illumination value, whether it is the SNI 7391:2008 standard or not, by means of measurements and simulations on the Jenderal Sudirman Pemalang road. measurement using a digital lux meter (AS803) and simulation using the software DIALux evo 10.1. Based on simulation results with the SNI 7391:2008 standard and an illumination value of 11-20 lux, the study recommends replacing the installed lamp with a 70 W LED lamp. The result of this study is that replacing a 70 W LED lamp can reduce the cost of electrical energy consumption by Rp 3,037,338 and reduce electrical power consumption by 2,102.4 kWh